An effector Peptide family required for Drosophila toll-mediated immunity. - Clemmons, A.W.; Lindsay, S.A.; Wasserman, S.A. (PLoS Pathogens, 2015)
In Drosophila melanogaster, recognition of an invading pathogen activates the Toll or Imd signaling pathway, triggering robust upregulation of innate immune effectors. Although the mechanisms of pathogen recognition and signaling are now well understood, the functions of the immune-induced transcriptome and proteome remain much less well characterized. Through bioinformatic analysis of effector gene sequences, we have defined a family of twelve genes - the Bomanins (Boms) - that are specifically induced by Toll and that encode small, secreted peptides of unknown biochemical activity. Using targeted genome engineering, we have deleted ten of the twelve Bom genes. Remarkably, inactivating these ten genes decreases survival upon microbial infection to the same extent, and with the same specificity, as does eliminating Toll pathway function. Toll signaling, however, appears unaffected. Assaying bacterial load post-infection in wild-type and mutant flies, we provide evidence that the Boms are required for resistance to, rather than tolerance of, infection. In addition, by generating and assaying a deletion of a smaller subset of the Bom genes, we find that there is overlap in Bom activity toward particular pathogens. Together, these studies deepen our understanding of Toll-mediated immunity and provide a new in vivo model for exploration of the innate immune effector repertoire.